RANCANG BANGUN TRAINER SISTEM KELISTRIKAN SENSOR PARKIR PADA MOBIL - Budiyono, Budiyono; Prasetyo, Imam; Setyo Prabowo, Joko (Universitas Muhammadiyah Pekajangan Pekalongan, 2019)
Now, to make it easier for drivers to park their vehicles, vehicle manufacturers have installed parking sensors, to keep pace with the development of the automotive world, students need to learn about parking sensors and also to support automotive electrical courses, it is necessary to make a trainer to make it easier for students to learn. is to make a trainer or learning media to make it easier for students to practice the parking sensor electrical system and understand how it works, the damage that often occurs and also know the maintenance that needs to be done to maintain the parking sensor. The result of making this parking sensor electrical system trainer is this trainer can be used as a practice medium to facilitate the parking sensor material and make it easier for students to understand the system.Keywords: Trainer, Electricity, Parking Sensor, Car